MILITARIZATION OF THE NATIONAL ECONOMY OF UKRAINE IN THE CONDITIONS OF WAR: CHALLENGES AND LIMITATIONS (INNOVATIVE ECONOMY, 2025)
Prints V.A. MILITARIZATION OF THE NATIONAL ECONOMY OF UKRAINE IN THE CONDITIONS OF WAR: CHALLENGES AND LIMITATIONSPurpose. The aim of the article is to identify the specifics of the militarization of the national economy of Ukraine in wartime and to analyse its main challenges and limitations for ensuring the economic stability of the state.Methodology of research. The theoretical and methodological basis of the study is a combination of general scientific and special methods, which allowed to reveal the specifics of the militarization of the national economy of Ukraine on the basis of a systematic approach. Methods of analysis and synthesis were used to study macroeconomic indicators of the militarization of the economy and identify the main challenges. Methods of logical generalization and abstraction were used to formulate conclusions and identify key trends in the militarization processes. The institutional method made it possible to argue the need for institutional reforms to ensure the sustainable development of the militarized economy. Content analysis of scientific sources and statistical reports was used to develop the empirical base.Findings. The content of the modern militarization of the Ukrainian economy was revealed as a multidimensional process that encompasses not only defence financing, but also the reformatting of the production structure, labour market, and state policy. An unprecedented increase in military spending (up to 36–39% of GDP), the intensification of the defence-industrial complex, and the increase in state defence orders were established. A number of critical limitations were identified ‒ deindustrialization, import dependence, fiscal overstrain, personnel shortage, and institutional imbalances.Originality. For the first time, based on a comprehensive approach, macroeconomic indicators of militarization in conditions of a protracted armed conflict were systematized, the structural parameters of the national military economy were clarified, and systemic challenges that affect ensuring the economic stability of the state were detailed.Practical value. The obtained results can be used in the formation of economic security strategies, the development of state programs for the modernization of the defence industry, the improvement of financial planning in the field of national security, as well as in the process of adapting Ukraine's economic policy to NATO and EU standards. Key words: militarization of the economy, defence-industrial complex, military economy, state defence order, economic security, fiscal constraints, strategic modernization.
Keywords: militarization of the economy; defence-industrial complex; military economy; state defence order; economic security; fiscal constraints; strategic modernization